Influence Of Digital Marketing And Product Variations With Brand Image As Moderating Variables On Purchase Decisions (Case Study Of Deta Yamaha Sukabumi) - Septiani, Ririn Dwi (Journal of Social Studies Arts and Humanities (JSSAH), 2023)
This study aims to find out (1) the effect of digital marketing on purchasing decisions, (2) the effect of product variations on purchasing decisions, (3) whether brand image can moderate the relationship between digital marketing and purchasing decisions, and (4) whether brand image can moderate the relationship between product variations and Purchase Decisions. This research uses descriptive associative quantitative approach. The population in this study are consumers who make  purchases of motorbikes at the Deta Yamaha Sukabumi Dealer, the number of samples taken is 122  respondents. The sampling technique in this research is random sampling. The method of collecting data using a questionnaire method which is measured using a Likert scale. The analytical technique used in this research is path analysis and MRA which is processed using SPSS 25. The results show that there is a positive and significant influence between digital marketing on purchasing decisions with a path coefficient value of = 0.724. There is a positive and significant effect between product variations on purchasing decisions with a path coefficient value of = 0.642. Brand image is able to moderate and strengthen the influence of digital marketing on purchasing decisions with a Moderated Regression Analysis (MRA) value of 0.355. Brand image is able to moderate and strengthen the influence of product variations on purchasing decisions with a Moderated Regression Analysis (MRA) value of 0.532.